2019
DOI: 10.1371/journal.pone.0225771
|View full text |Cite
|
Sign up to set email alerts
|

Gender-based differences in platelet function and platelet reactivity to P2Y12 inhibitors

Abstract: BackgroundGender influences platelet biology. Women have a larger platelet count, but gender-based differences in platelet function remain debated. We performed a study addressing gender-based differences in platelet function using point-of-care platelet function tests (PFT).MethodsThe patient population consisted of 760 cardiac surgery patients where preoperative PFT (multiple-electrode aggregometry [MEA]) were available. Platelet count and function at the ADPtest and TRAPtest were compared in the overall pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 33 publications
3
37
0
Order By: Relevance
“…Additionally, as discussed previously, platelets store and release BDNF 71 , 72 . In this sense, classic and emerging studies show that women have higher platelet content than men 98 100 . In light of this, we do not discard that platelet count could contribute to a higher BDNF response in women compared with men (Table 2 ).…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, as discussed previously, platelets store and release BDNF 71 , 72 . In this sense, classic and emerging studies show that women have higher platelet content than men 98 100 . In light of this, we do not discard that platelet count could contribute to a higher BDNF response in women compared with men (Table 2 ).…”
Section: Discussionmentioning
confidence: 95%
“…The mechanism of this relationship is unclear, although sex differences in platelet function have been reported since 1975 [14]. Evidence demonstrated that compared to male patients, females have higher platelet counts and enhanced platelet activation [15,16,23,26], which may be potential reasons. As discussed, platelet plays a pivotal role in inflammation via a variety of pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, there is an important difference in platelet biology impacted by sex. It has been reported that the sexual diversity in platelet sensitivity may be intrinsic to the platelet [14], and females showed a higher platelet reactivity than males [15,16]. This feature suggests that the prognostic value of MPV in SP patients may be differed by sex.…”
Section: Introductionmentioning
confidence: 95%
“…Our statistical analysis showed lower levels of platelets in men than in women and this result is in line with previous findings. The gender influence on platelet biology was shown several years ago [26] and recent studies reported a higher number of fibrinogen surface receptors and a greater ability to bind fibrinogen in women [27]. In addition, estrogens have been shown to enhance platelet production [28].…”
Section: Discussionmentioning
confidence: 99%